A Modeling Strategy for Predicting the Response of Steel Plate-Concrete Composite Walls - Mohammad Sadegh Barkhordari (Journal of Rehabilitation in Civil Engineering)
Shear walls are among lateral load resisting systems which are used to provide adequate stiffness, strength, and nonlinear deformation capacity to withstand strong ground motion. Usually at the base of the wall, these structures tolerate inelastic deformations subjected to strong ground motions. Researchers have offered composite walls to solve these problems. Steel plate-concrete composite (SCC) walls have been regarded as an alternative to reinforced concrete walls in terms of seismic performance and constructability. In this study, a new semi-macro modified fixed strut angle finite element model is proposed to predict the nonlinear response of SCC walls using OpenSees. A new modified fixed strut angle model and a quadrilateral flat shell element are adapted to the analysis of SCC shear walls. The numerical model is validated using the results of a set of experimental data reported in the literature. Comprehensive comparisons between analytical-model-predictions and experimental data suggest that the numerical model can accurately simulate the steel plate-concrete composite wall responses.